# The form of subgroups A (n, <[bar.a]>) and B(n, <[bar.a]>) on additive group [Z.sub.m].

1. Introduction

Let G be additive Abelian group and H is a subgroup of G. For positive integer n, we defined

A(n, H) = {x [member of] G: nx [member of] H} and B(n, H) = {y [member of] G: y = nx [there exists] x [member of] H}

[Z.sub.m] is the additive group of residue classes modulo m under the operation [bar.a] + [bar.b] = [bar.a + b] for [bar.a], [bar.b] [member of] [Z.sub.m].

If a [member of] G, then <[bar.a]> = {ka: k [member of] Z) is the subgroup generated by a.

2. Preliminaries

Theorem 2.1 Let [bar.a], [bar.b] [member of] [Z.sub.m], [bar.a] = [bar.b] if and only if m|(a - b).

Theorem 2.2 If [bar.a] [member of] [Z.sub.m] and k [member of] Z, then k[bar.a] = [bar.ak].

Theorem 2.3 Let a, b, c [member of] Z. If a|bc and gcd(a, b) = 1, then a|c.

Theorem 2.4 Let a, b, d, q, r [member of] Z.

If gcd(a, b) = d such that a = qd and b = rd, then gcd(q, r) = 1.

Theorem 2.5 If gcd(a, b) = d, then ax + by = d for some x, y [member of] Z.

Theorem 2.6 gcd(a, b) x lcm(a, b) = [absolute value of ab].

3. Properties of A(n, H) and B(n, H) on additive Abelian group G

Theorem 3.1 B(n, H) [subset or equal to] H [subset or equal to] A(n, H).

Proof. If y [member of] B(n, H), then y = nx for some x [member of] H. But H is closed, so nx [member of] H and y [member of] H.

If x [member of] H, then nx [member of] H, and we get that x [member of] A(n, H). Thus B(n, H) [subset or equal to] H [subset or equal to] A(n, H).

Theorem 3.2 A(1, H) = B(1, H) = H.

Proof. If x [member of] A(1,H), then 1x [member of] H that is x [member of] H. Thus A(1,H) [subset or equal to] H but H [subset or equal to] A(1, H). So A(1, H) = H.

If x [member of] H, then x = 1x and x [member of] B(1, H). So H [subset or equal to] B(1, H) but B(1, H) [subset or equal to] H.

Theorem 3.3 A(n, H) and B(n, H) are the subgroups of an additive Abelian group G.

Proof. Let x, y [member of] A(n, H). We get that nx [member of] H and n y [member of] H. Since H is closed and commute, so nx - ny [member of] H such that n(x - y) = nx - ny [member of] H, thus x - y [member of] A(n, H). So A(n, H) is the subgroup of G. Let x, y [member of] B(n, H). We get that x = na and y = nb for some a, b [member of] H. So a - b [member of] H and x - y = na - nb = n(a - b), so x - y [member of] B(n, H). Thus B(n,H) is the subgroup of G.

Remark 3.1 It is easy to proved that A(n, G) = G and B(n, {0)) = {0).

Theorem 3.4 Let [H.sub.1] and [H.sub.2] be subgroup of G, then

1. If [H.sub.1] [subset or equal to] [H.sub.2], then A(n, [H.sub.0] [subset or equal to] A(n, [H.sub.2]) and B(n, [H.sub.0] [subset or equal to] B(n, [H.sub.2]).

2. A(n, [H.sub.1] [intersection] [H.sub.2]) = A(n, [H.sub.1] [intersection] A(n, [H.sub.2]) and B(n, [H.sub.1] [intersection] [H.sub.2]) [subset or equal to] B(n, [H.sub.1]) [intersection] B(n, [H.sub.2]).

Proof. 1. Assume that [H.sub.1] [subset or equal to] [H.sub.2] and let x [member of] A(n, [H.sub.1]). Then nx [member of] [H.sub.1] but [H.sub.1] [subset or equal to] [H.sub.2], so nx [member of] [H.sub.2], so x [member of] A(n, [H.sub.2]). Thus A(n, [H.sub.1]) [subset or equal to] A(n, [H.sub.2]). Let ye B(n, [H.sub.1]) we get y = nx for some x [member of] [H.sub.1] but [H.sub.1] [subset or equal to] [H.sub.2], so x [member of] [H.sub.2]. Thus y [member of] B(n, [H.sub.2]), and so B(n, [H.sub.1]) [subset or equal to] B(n, [H.sub.2]).

2. [MATHEMATICAL EXPRESSION NOT REPRODUCIBLE IN ASCII]

Thus A(n, [H.sub.1] [intersection] [H.sub.2]) = A(n, [H.sub.1]) [intersection] A(n, [H.sub.2]).

Let y [member of] B(n, [H.sub.1] [intersection] [H.sub.2]). Then y = nx for some x [member of] [H.sub.1] [intersection] [H.sub.2], therefore y = nx such that x [member of] [H.sub.1] and x [member of] [H.sub.2]. So y = nx, x [member of] [H.sub.1] and y = nx, x [member of] [H.sub.2] we get that y [member of] B(n, [H.sub.1]) and y [member of] B(n, [H.sub.2]). Thus y [member of] B(n, [H.sub.1]) [intersection] B(n, [H.sub.2]). Hence B(n, [H.sub.1] [intersection] [H.sub.2]) [subset or equal to] B(n, [H.sub.1]) [intersection] B(n, [H.sub.2]).

Remark 3.2 If [H.sub.1] [subset or equal to] [H.sub.2], then B(n, [H.sub.1] [intersection] [H.sub.2]) = B(n, [H.sub.1]) [intersection] B(n, [H.sub.2]).

4. Main Results

For [bar.a] [member of] [Z.sub.m], <[bar.a]> is the subgroup of [Z.sub.m] which generated by [bar.a].

Theorem 4.1 B(n, <[bar.a]>) = <[bar.na]>.

Proof. Let [bar.y] [member of] B(n, <[bar.a]>), then [bar.y] = [bar.nx] for some x [member of] <[bar.a]>. Since [bar.x] [member of] <[bar.a]>, we get [bar.x] = [bar.ka] for some k [member of] [Z.sup.+] [union] {0}. So [bar.y] = [bar.nx] = nk[bar.a] = kn[bar.a] = k[bar.na] [member of] <[bar.na]>, thus B(n, <[bar.a]>) [subset or equal to] <[bar.na]>. Let [bar.y] [member of] <[bar.na]>, then [bar.y] = k[bar.na] for some k [member of] [Z.sup.+] [union] {0}. We get [bar.y] = k[bar.na] = kn[bar.a] = n(k[bar.a]) such that k[bar.a] [member of] <[bar.a]>. So [bar.y] [member of] B(n,<[bar.a]>), and thus <[bar.na]> [subset or equal to] B(n, <[bar.a]>). Hence B(n, <[bar.a]>) = <[bar.na]>.

Corollary 4.1 B(n, [Z.sub.m]) = <[bar.n]>.

Proof. We known that [Z.sub.m] = <[bar.1]>. Thus B(n, [Z.sub.m]) = B(n, <[bar.1]>) = <[bar.n x 1]> = <[bar.n]>.

Theorem 4.2 If a|m, then [MATHEMATICAL EXPRESSION NOT REPRODUCIBLE IN ASCII].

Proof. Assume that a|m and let gcd(n, a) = d. We get d|n and d|a, therefore n = d[x.sub.1] and a = d[x.sub.2] for some [x.sub.1], [x.sub.2] [member of] [Z.sup.+]. And we get that a/d = [x.sub.2] and gcd([x.sub.1], [x.sub.2]) = 1. Since a|m so m = a[x.sub.3] for some [x.sub.3] [member of] [Z.sup.+]. Now I want to show that A(n, <[bar.a]>) = <[[bar.x].sub.2]>.

Let [bar.x] [member of] A(n, <[bar.a]>). We get n[bar.x] [member of] <[bar.a]>, so n[bar.x] = k[bar.a] for some k [member of] [Z.sup.+] [union] {0) and then [bar.nx] = [bar.ka]. Therefore m|(nx - ka), thus nx - ka = mq for some q [member of] Z. So nx = ka + mq = ka+ a[x.sub.3]q = a(k+ [x.sub.3]q), and then d[x.sub.1]x = d[x.sub.2](k+ [x.sub.3]q) so [x.sub.1]x = [x.sub.2](k+ [x.sub.3]q), that is [x.sub.2]|[x.sub.1]x. Since gcd([x.sub.1], [x.sub.2]) = 1, thus [x.sub.2]|x that is [bar.x] [member of] < [[bar.x].sub.2]>. Hence A(n, <[bar.a]>) [subset or equal to] <[[bar.x].sub.2]]>.

Let [bar.x] [member of] <[[bar.x].sub.2]>. Then [bar.x] = k[[bar.x].sub.2] for some k [member of] [Z.sup.+] [union] {0}, so n[bar.x] = nk[[bar.x].sub.2] = d[x.sub.1]k[[bar.x].sub.2] and we get [bar.nx] = [bar.d[x.sub.1]]k[[bar.x].sub.2]. Therefore m|(nx - d[x.sub.1]k[x.sub.2]) that is nx - d[x.sub.1]k[x.sub.2] = mq for some q [member of] Z. And we get nx = d[x.sub.2] k[x.sub.1] + mq = a k [x.sub.1] + a[x.sub.3]q = a(k [x.sub.1] + [x.sub.3]q), this mean a | nx. Thus n[bar.x] = [bar.nx] [member of] <[bar.a]>. So [bar.x] [member of] A(n, <[bar.a]>), and we get that <[[bar.x].sub.2] > [subset or equal to] A(n, <[bar.a]>). Hence [MATHEMATICAL EXPRESSION NOT REPRODUCIBLE IN ASCII].

Lemma 4.3 Let [bar.a] [member of] [Z.sub.m], if gcd(a, m) = d then <[bar.a]> = <[bar.d]>.

Proof. Assume that gcd(a,m) = d. We get d|a and d|m, therefore a = d[k.sub.1] for some [k.sub.1] [member of] [Z.sup.+] [union] {0} and m = d[k.sub.2] for some [k.sub.2] [member of] [Z.sup.+].

Let [bar.x] [member of] <[bar.a]>. Then [bar.x] = k[bar.a] for some k [member of] [Z.sup.+] [union] {0), thus [bar.x] = k[bar.a] and then m|(x ka). Therefore x - ka = mq for some q [member of] Z, then x = ka + mq = kd[k.sub.1] + d[k.sub.2]q = d(k[k.sub.1] + [k.sub.2]q). So d|x and we get x [member of] <[bar.d]>. Thus <[bar.a]> [subset or equal to] <[bar.d]>.

Since gcd(a, m) = d, we get that ax+ my = d for some x, y [member of] Z. Then ax - d = - my = m(-y) such that -y [member of] Z. Thus m|(ax - d), we get [bar.ax] = [bar.d] and so <[bar.xa]> = <[bar.ax]> = <[bar.d]>

Note that, it is easy to see that <[bar.xa]> [subset or equal to] <[bar.a]>. Thus <bar.d> [subset or equal to]<[bar.a]>. Hence <[bar.a]> = <[bar.d]>.

Theorem 4.3 [MATHEMATICAL EXPRESSION NOT REPRODUCIBLE IN ASCII] where gcd(a,m) = d.

Proof. Since gcd(a,m) = d, we get that d|m and <[bar.a]> = <[bar.d]>. Thus [MATHEMATICAL EXPRESSION NOT REPRODUCIBLE IN ASCII] because d | m.

We known that gcd(n,d) x lcm(n,d) = nd, or gcd(n, d) = nd/lcm(n,d). Therefore d/gcd(n,d) = d/[nd/lcm(n,d)] = d x [lcm(n, d)/nd] = [lcm(n, d/n)]

Thus [MATHEMATICAL EXPRESSION NOT REPRODUCIBLE IN ASCII].

Corollary 4.3 [MATHEMATICAL EXPRESSION NOT REPRODUCIBLE IN ASCII]. And if gcd(n, m) = 1, then A(n, {[bar.0])} = {[bar.0]}.

Proof. We known that {[bar.0]} = <[bar.0]>, and since gcd(0,m) = m.

Thus [MATHEMATICAL EXPRESSION NOT REPRODUCIBLE IN ASCII].

And if gcd(n, m) = 1, then A(n, {[bar.0])} = <[bar.m]/1> = <[bar.m]> = <[bar.0]> = {[bar.0]).

Example In [Z.sub.20] = {[bar.0], [bar.1], [bar.2], [bar.3],...,[bar.19])

B(18, <[bar.15]>) = <[bar.18 x 15]> = <[bar.270]> = <[bar.10]>.

A(18, <[bar.15]>) = ?

Since gcd(15, 20) = 5 and gcd(18, 5) = 1.

Thus A(18, <[bar.15]>) = <[bar.5]/1> = <[bar.5]>.

References

 Ivan Niven, Herbert S. Zuckerman and Hugh L. Montgomery (1960). An Introduction To The Theory of Numbers. candana. John Wiley & Sons, Inc.

 Marie J. Weiss and Roy Dubisch. (1962). Higher Algebra for the Undergraduate. Japan.Toppan Printing company, LTD.

 R. P. Sullivan. (2004). Msc Projects on Semigroup. School of Mathematics & Statistics The University of Western Australias.

 Thomas W. Hungerford. (1974). Algebra. New York. Springer Verlag.

 W. Keith Nicholson. (1999). Introduction to Abstract algebra second Edition. Cannada. John Wiley & Sons, Inc.

Author: Printer friendly Cite/link Email Feedback Sommanee, Worachead Global Journal of Pure and Applied Mathematics Report 9THAI Aug 1, 2010 2165 Sensitivity of estimators to three levels of correlation between error terms. Time series forecasting method in uncertain environment. Abelian groups Integers